2017
DOI: 10.1038/ismej.2017.58
|View full text |Cite
|
Sign up to set email alerts
|

Characterising and predicting cyanobacterial blooms in an 8-year amplicon sequencing time course

Abstract: Cyanobacterial blooms occur in lakes worldwide, producing toxins that pose a serious public health threat. Eutrophication caused by human activities and warmer temperatures both contribute to blooms, but it is still difficult to predict precisely when and where blooms will occur. One reason that prediction is so difficult is that blooms can be caused by different species or genera of cyanobacteria, which may interact with other bacteria and respond to a variety of environmental cues. Here we used a deep 16S am… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
80
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(88 citation statements)
references
References 109 publications
8
80
0
Order By: Relevance
“…To investigate node-environment relationships, we used an environmental data matrix that 161 included: particulate phosphorus in ”g/ L (PP, the difference between TP and DP), particulate 162 nitrogen in mg/ L (PN, the difference between TN and DN), soluble reactive phosphorus in ”g/ L 163 (DP), dissolved nitrogen in mg/ L (DN), 1-week-cumulative precipitation in mm and 1-week-164 average air temperature in Celsius. The measurements of the different environment variables are 165 described in Tromas et al (2017). In this previous study, we showed that these environmental 166 variable, over the 8 years, were not correlated with one another.…”
Section: Node-environment Relationships Analysis 160mentioning
confidence: 92%
See 1 more Smart Citation
“…To investigate node-environment relationships, we used an environmental data matrix that 161 included: particulate phosphorus in ”g/ L (PP, the difference between TP and DP), particulate 162 nitrogen in mg/ L (PN, the difference between TN and DN), soluble reactive phosphorus in ”g/ L 163 (DP), dissolved nitrogen in mg/ L (DN), 1-week-cumulative precipitation in mm and 1-week-164 average air temperature in Celsius. The measurements of the different environment variables are 165 described in Tromas et al (2017). In this previous study, we showed that these environmental 166 variable, over the 8 years, were not correlated with one another.…”
Section: Node-environment Relationships Analysis 160mentioning
confidence: 92%
“…we used 16S amplicon sequencing to broadly survey changes in the lake microbial community 97 over time, generally at the genus level (Tromas et al, 2017). Here, we use Minimum Entropy 98…”
Section: Traits 73mentioning
confidence: 99%
“…Mou et al (2013) found a positive association between microcystin degradation rates and Burkholderiales, suggesting a role for these bacteria in toxin breakdown. Burkholderiales are important in some cyanobacterial blooms (Louati et al, 2015), although a decline in abundance of a Burkholderiales strain can be predictive of the onset of a cyanobacterial bloom (Tromas et al, 2017). In the current study, samples with the anatoxin-a operon had fewer Burkholderiales, so it possible that the bacteria from this family in the Eel River mats are negatively impacted by toxin production (unfortunately, the genes for anatoxin-a degradation are not known, so this cannot be determined genomically).…”
Section: Microbial Assemblage and Anatoxin-amentioning
confidence: 68%
“…Cyanobacterial growth rates and other physiological process are often enhanced in the presence of co-occurring microbes (Allen, 1952), and few antagonisms between cyanobacteria and other bacteria have been reported (Paerl, 1996;Berg et al, 2009). The microbial assemblage of lakes shifts when cyanobacteria bloom (Woodhouse et al, 2016;Tromas et al, 2017), and the assemblage composition differs depending on the cyanobacterial species causing the bloom (Louati et al, 2015;Bagatini et al, 2014). With most interactions among Cyanobacteria and co-occurring bacteria facilitating cyanobacterial growth, identifying the diversity and metabolisms of the whole microbial consortia within toxigenic cyanobacterial mats is central to understanding the ecological processes that drive the proliferation of toxigenic mats in rivers.…”
Section: Introductionmentioning
confidence: 99%
“…We followed the same protocol described in the study by Tromas et al, (2017) to generate a library of V4 region amplicons. Libraries for 2 × 250 bp paired-end Illumina sequencing were prepared using a two-step 16S rRNA gene amplicon PCR as described in the study by Preheim et al (2013).…”
Section: Sequence Analysismentioning
confidence: 99%